2000
DOI: 10.1176/appi.ajp.157.8.1327
|View full text |Cite
|
Sign up to set email alerts
|

Heat Intolerance in Patients With Chronic Schizophrenia Maintained With Antipsychotic Drugs

Abstract: Schizophrenic patients maintained on antipsychotic drugs exhibit impaired heat tolerance. Possible explanations are a reduced ability to convey heat from the body's core to the periphery with or without excessive heat production. The hyperthermic response to the heat tolerance test may reflect a dysfunction associated with schizophrenia, a neuroleptic-induced side effect, or both.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 10 publications
3
32
0
Order By: Relevance
“…Thus, hypothetically, schizophrenia might be associated with a secondary or even a primary thermoregulatory dysfunction. This hypothesis is corroborated by accrued data which suggest that both drug-free and medicated schizophrenia patients may exhibit abnormal body/ core thermoregulation (Laborit 1979;Levinson and Simpson 1986;Dilsaver 1988;Heh et al 1988;Lazarus et al 1989;Cape 1994;Maeir et al 1994;Dixit et al 1997;Schwaninger et al 1998;Hermesh et al 2000aHermesh et al ,b, 2001Chong and Castle 2004).…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Thus, hypothetically, schizophrenia might be associated with a secondary or even a primary thermoregulatory dysfunction. This hypothesis is corroborated by accrued data which suggest that both drug-free and medicated schizophrenia patients may exhibit abnormal body/ core thermoregulation (Laborit 1979;Levinson and Simpson 1986;Dilsaver 1988;Heh et al 1988;Lazarus et al 1989;Cape 1994;Maeir et al 1994;Dixit et al 1997;Schwaninger et al 1998;Hermesh et al 2000aHermesh et al ,b, 2001Chong and Castle 2004).…”
Section: Introductionmentioning
confidence: 81%
“…Findings from preliminary studies in which we examined such putative thermoregulatory dysfunction in schizophrenia indicate, that untreated overtly psychotic schizophrenia patients exhibit substantial and significantly higher core (Hermesh et al 2000b;Shiloh et al 2001), body (Shiloh et al 2000), and corneal (Shiloh et al 2003a(Shiloh et al ,b, 2005) temperature compared to both healthy comparison subjects and antipsychotic drug (APD)-treated patients. Moreover, some data suggest that schizophrenia patients' mental status may also correlate with their core temperature (Shiloh et al 2003b(Shiloh et al , 2007.…”
Section: Introductionmentioning
confidence: 98%
“…8 Because heat removal is primarily dependent on CBF 8 and the arterio-venous temperature difference across the brain, 8,9 reduced cerebral perfusion relative to cerebral metabolism may indicate decreased central heat removal (i.e., higher BT). 10 Previous studies have suggested that schizophrenia patients have dysfunctional thermoregulation, [11][12][13][14][15][16][17] and these data suggest that patients with schizophrenia may exhibit abnormal BT.…”
Section: Introductionmentioning
confidence: 99%
“…Most clinical studies use rectal temperature as an indicator of core body temperature (Dauch and Bauer, 1990 ;Freedman and Woodward, 1996 ;Hermesh et al, 2000 ;Shiloh et al, 2001 ;Weibel et al, 1997) although corneal (Rysa and Sarvaranta, 1974), tympanic (Sato et al, 1996) or axillary (Henker and Coyne, 1995 ;Lefrant et al, 2003 ;Lodha et al, 2000) temperatures may also correlate with core body temperature. Among these, corneal temperature can be measured by non-invasive procedures and thus, can be used more easily with some patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%